Being a nursing student during the coronavirus pandemic: a mixed methods study - Gudrun Rohde; Berit Johannessen; Markus Maaseide; Sylvi Flateland; Anne Valen Skisland; Ellen Benestad Moi; Kristin Haraldstad (BMC, 2023)
Abstract Background The COVID-19 pandemic led to major changes in people's lives via protective strategies aimed at limiting the transmission of COVID-19, including social distancing, lockdowns, cancelled or limited leisure activities and tutorials and supervision for students taking place digital. All of these changes may have influenced students' health and quality of life. Aim To describe and explore fear of COVID-19 and psychological distress, as well as general health and quality of life, among baccalaureate nursing students at 1 year into the COVID-19 pandemic. Method We used a mixed method study design, including quantitative data from University of Agder, data that was a part of a national survey of baccalaureate nursing students nearly one year into the pandemic. All the nursing students at the university were invited to take part between 27 January and 28 February 2021. The quantitative survey included 396 (out of total 858) baccalaureate nursing students (response rate: 46%). The quantitative data were collected using well-validated measures of fear of COVID-19, psychological distress, general health and quality of life, and the data were analysed using the ANOVA-tests for continuous data and chi-square tests for categorical data. Qualitative data were gathered from focus group interviews from the same university two-three months later. Five focus group interviews were conducted with a total of 23 students (7 men, 16 women). The qualitative data were analysed using systematic text condensation. Results The mean score (standard deviation [SD]) for fear of COVID-19 was 2.32 (0.71), for psychological distress was 1.53 (1.00), for general health was 3.51 (0.96) and for overall quality of life was 6.01 (2.06). In the qualitative data, we identified the overarching theme effect of COVID-19 on students' quality of life and the three main themes; importance of personal relations, physical health challenges and mental health challenges. Conclusion The COVID-19 pandemic influenced negatively nursing students' quality of life and physical and mental health, and they often felt lonely. However, most of the participants also adapted strategies and resilience factors to cope with the situation. Via the pandemic situation, the students learned additional skills and mental mindsets that may be useful in their future professional lives.